Association between serum LH levels on hCG trigger day and live birth rate after fresh embryo transfer with GnRH antagonist regimen in different populations - Zhou, Ruiqiong; Dong, Mei; Huang, Li; Zhu, Xiulan; Wei, Jinyan; Zhang, Qianyu; Liu, Dun; Zhang, Xiqian; Liu, Fenghua (Frontiers in Endocrinology, 2023)
Objective: To investigate whether serum LH levels on hCG trigger day are associated with live birth rate (LBR) after fresh embryo transfer with GnRH antagonist regimen in different populations. Methods: This study was a retrospective study. A total of 3059 fresh embryo transfers were divided into three populations: predicted normal ovarian responders (NOR) (n=2049), patients with PCOS (n=533), and predicted poor ovarian responders (POR) (n=477). Each population was stratified into three groups based on LH levels: < 25th percentile, 25–75th percentile, and > 75th percentile. The primary outcome of the study was LBR, and secondary outcomes included implantation, clinical pregnancy, and early pregnancy loss rates. Univariable and multivariable regression analyses were performed to adjust for potential confounders. Results: In NOR, compared to the reference group (＞75th percentile), LBR was significantly lower in the < 25th percentile group (adjusted OR=0.662; 95%CI, 0.508-0.863) and 25-75th percentile group (adjusted OR=0.791; 95%CI, 0.633-0.988). In PCOS patients, LBR decreased significantly in the < 25th percentile group (41.4%) compared to the 25-75th percentile group (53.7%) and > 75th percentile group (56.1%). In addition, the LBR was lower in the < 25th percentile group (33.6%) compared with the 25-75th percentile group (43.4%) and the＞75th percentile group (42.0%) in POR, but this was not statistically significant. Conclusions: High serum LH levels are associated with increased LBR after fresh embryo transfer in GnRH antagonist cycles, which may be attributable to higher implantation rate. LH may be a predictor of whether to schedule fresh embryo transfer in IVF cycles for better clinical outcomes. Keywords: luteinizing hormone, GnRH antagonist, live birth rate, controlled ovarian stimulation, ovarian response.